Genome‐wide effect of pulmonary airway epithelial cell–specific Bmal1 deletion. Issue 5 (22nd February 2019) - Zhang, Zhenguang; Hunter, Louise; Wu, Gang; Maidstone, Robert; Mizoro, Yasutaka; Vonslow, Ryan; Fife, Mark; Hopwood, Thomas; Begley, Nicola; Saer, Ben; Wang, Ping; Cunningham, Peter; et al.
ABSTRACT: Pulmonary airway epithelial cells (AECs) form a critical interface between host and environment. We investigated the role of the circadian clock using mice bearing targeted deletion of the circadian gene brain and muscle ARNT‐like 1 ( Bmal1 ) in AECs. Pulmonary neutrophil infiltration, biomechanical function, and responses to influenza infection were all disrupted. A circadian time‐series RNA sequencing study of laser‐captured AECs revealed widespread disruption in genes of the core circadian clock and output pathways regulating cell metabolism (lipids and xenobiotics), extracellular matrix, and chemokine signaling, but strikingly also the gain of a novel rhythmic transcriptome in Bmal1 ‐targeted cells. Many of the rhythmic components were replicated in primary AECs cultured in air‐liquid interface, indicating significant cell autonomy for control of pulmonary circadian physiology. Finally, we found that metabolic cues dictate phasing of the pulmonary clock and circadian responses to immunologic challenges. Thus, the local circadian clock in AECs is vital in lung health by coordinating major cell processes such as metabolism and immunity.—Zhang, Z. Hunter, L., Wu, G., Maidstone, R., Mizoro, Y., Vonslow, R., Fife, M., Hopwood, T., Begley, N., Saer, B., Wang, P., Cunningham, P., Baxter, M., Durrington, H., Blaikley, J. F., Hussell, T., Rattray, M., Hogenesch, J. B., Gibbs, J., Ray, D. W., Loudon, A. S. I. Genome‐wide effect of pulmonary airway epithelial cell‐specific Bmal1 deletion. FASEB J. 33, 6226–6238 (2019). www.fasebj.org